PENGARUH STRUKTUR PASAR, KOMPETISI, DIVERSIFIKASI, KAPITALISASI, RISIKO KREDIT, DAN SIZE TERHADAP PROFITABILITAS BANK (Studi pada Bank Umum Konvensional di Indonesia Periode 2009-2013) - Wahyu Widiasari, Febrina; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2015)
This study is conducted to examine the determinants of conventional commercial banks profitability in Indonesia for the period 2009 to 2013. The purpose of this study was to analyze the influence of market share, competition, diversification, capitalization (equity to total asset ratio), credit risk (non performing loans), and size toward Return on Asset (ROA) as a measure of bank profitability. The analysis technique used is Ordinary Least Square (OLS) method of multiple linear regression. The results are (1) market share on deposits has positive significant effect on ROA. (2) lerner index has positive significant effect ROA (3) HHI diversification has positive significant effect on ROA. (4) capitalization has positive significant effect on ROA.(5) credit risk has negative significant effect on ROA. (6) size has positive significant effect on ROA.